USING THE OUTSOURCING MECHANISM TO INCREASE THE EFFICIENCY OF REPAIR AND MAINTENANCE IN METALLURGICAL ENTERPRISES - Elena I. Kozlova; Anna N. Lopatina; Maxim A. Novak (Вестник Дагестанского государственного технического университета: Технические науки)
Abstract. Objectives The aim of the work is to study the outsourcing mechanism from the point of view of increasing the efficiency of repair and maintenance at a metallurgical enterprise. Method Analysis of the experience of using outsourcing of repair services at domestic and foreign metallurgical enterprises was carried out. Analysis of the experience of the withdrawal from enterprise repair services into a separate outsourcing company has shown that the main advantages of this method of organising repair activities are an increase in the transparency of the costs of repairs and maintenance, and hence their reduction, as well as a reduction in the amount of equipment downtime. The main characteristics of outsourcing were revealed, substantiating its expediency. The restructuring of the repair system provides a step-by-step transition from decentralised to centralised structures of technical, mechanical, power and electrical repair services of enterprises, from the principle of "self-service" to the principle of "proprietary service" by isolating the subdivisions of the repair system from the structure of enterprises and creating competing members of the repair services market. Put another way, this is typified by moving away from the status of auxiliary production to a selfdependent activity. The stages of outsourcing the repair services of the enterprise are considered and possible problems that may arise in the course of the work of a working group are established to determine the suitability of outsourcing and to resolve the numerous issues arising from the transfer of repair functions. Results The findings of the research include approaches developed for overcoming risky situations: providing guarantees from the customer and the contractor and indicating them in the contract, increasing the motivation of the outsourcing company through a key performance indicator that should increase the interest of the performer in providing quality services to the customer. Conclusion As a result of the research it was revealed that the implementation of outsourcing requires concerted action from the customer and the outsourcer. Outsourcing is a new approach to managing the costs of repair and maintenance of the main equipment. The transfer of repair functions to outsourcing helps the enterprise to operate the service object economically and achieve its goals.